How the Health Advocate Role is reflected in health professions education literature: A scoping review protocol - Duong, Khoa; Quaiattini, Andrea; Young, Meredith (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
The Health Advocate Role remains challenging to teach, assess, and study. Mapping the health professions education (HPE) literature—while considering the influence of context—can offer a more nuanced understanding of how the role is conceptualized and enacted across the HPE landscape. This scoping review aims to support the contextualized implementation of the Health Advocate Role.